2020
DOI: 10.1016/j.psj.2019.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin on ochratoxin A–induced liver oxidative injury in duck is mediated by modulating lipid metabolism and the intestinal microbiota

Abstract: Curcumin has antioxidant functions, regulates the intestinal microbial composition, and alleviates mycotoxin toxicity. The present study aimed to explore whether curcumin could alleviate ochratoxin A ( OTA )-induced liver injury via the intestinal microbiota. A total of 720 mixed-sex 1-day-old White Pekin ducklings were randomly assigned into 4 groups: CON (control group, without OTA), OTA (fed a diet with 2 mg/kg OTA), CUR (ducks fed a diet with 400 mg/kg curcumin), and OTA + CUR (2 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 70 publications
10
41
0
Order By: Relevance
“…Indeed, Zhai et al [99] explored the effect of curcumin on ochratoxin-induced liver oxidative injury in an animal model of liver disease. A total of 720 ducks were randomly assigned into four different groups: control, ochhratoxin, curcumin (ducks fed a diet with 400 mg/kg curcumin), and ochhratoxin plus curcumin and treated for 21 days.…”
Section: Curcumin Favors Beneficial Bacterial Strains In Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Zhai et al [99] explored the effect of curcumin on ochratoxin-induced liver oxidative injury in an animal model of liver disease. A total of 720 ducks were randomly assigned into four different groups: control, ochhratoxin, curcumin (ducks fed a diet with 400 mg/kg curcumin), and ochhratoxin plus curcumin and treated for 21 days.…”
Section: Curcumin Favors Beneficial Bacterial Strains In Gut Microbiotamentioning
confidence: 99%
“…The authors demonstrated that curcumin counteracted ochhratoxin-induced oxidative injury and lipid metabolism disruption. By 16S rRNA gene sequencing of gut microbiota it was shown that curcumin supplementation was also able to neutralize the decrease in butyric acid-producing bacteria induced by ochratoxin, and increased the richness and diversity of gut microbiota [99]. Thus, the authors hypothesized that curcumin could alleviate liver oxidative injury by modulating the gut microbiota.…”
Section: Curcumin Favors Beneficial Bacterial Strains In Gut Microbiotamentioning
confidence: 99%
“…Sayrafi et al [14] clarified that the declined the liver enzyme activity following supplementation with nanocurcumin may be due to its antioxidant properties. Curcumin has an antioxidant function and adjusts the intestinal microbial composition [15]. Furthermore, Partovi et al [16] stated that nanocurcumin at a level of 300 mg/kg diet can be used in poultry production as a good feed additive.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of GSH-Px and T-AOC in the jejunum mucosal of ducks which fed dietary curcumin increased linearly (P < 0.001) and quantically (P < 0.001), and the MDA content decreased linearly (P < 0.05) owing the dietary curcumin supplementation [27]. A study of Zhai et al [28] revealed that curcumin supplementation increased the activity of T-AOC (P > 0.05), T-SOD (P < 0.05) and…”
Section: Discussionmentioning
confidence: 95%